Predictors of Acute Stent Thrombosis After Primary Percutaneous Coronary Intervention - Ikram Ullah; Amir Rashid Qureshi; Sami Ullah; Mohammad Asghar Khan; Muhammad Salman; Hamid Ali Shah (Gandhara University, 2023)
OBJECTIVES To identify the speciﬁc predictors of acute stent thrombosis in patients after primary percutaneous coronary intervention. METHODOLOGY This retrospective study was carried out at the Department of Cardiology Hayatabad Medical Complex Peshawar from 1st January to 30th June 2022. All consecutive patients with an angiographically conﬁrmed stent thrombosis were enrolled. Patients gave informed consent for the inclusion of data in this registry. Stent thrombosis was categorized according to the timing of the event as acute (occurrence within the ﬁrst 24 hours after the index procedure). RESULTS A total of 400 patients were included in the study. Age ranged between 35-70 years, with a mean age of 52.5. There were 260(65%) males and 140(35%) females, with male to female ratio of 1.8:1. All patients underwent primary PCI with stent implantation. According to the elapsed time since stent implantation, 42(10.5%) patients presented with acute stent thrombosis after primary percutaneous coronary intervention. The mean time to develop acute stent thrombosis after primary PCI was ±4.5 hours (range 3-6 hours). In most STEMI patients, 340(85%) received a loading dose of clopidogrel at the time of the index PCI. In 23(54.7%) patients, acute stent thrombosis occurred within 6 hours, 10(23.8%) within 12 hours, 6(14.2%) within 18 hours and 3(7.1%) after clopidogrel loading. CONCLUSION Inadequate stent expansion or mal-opposition, diabetes mellitus, chronic kidney disease, and female gender were the strong predictors of acute stent thrombosis.